EL CORAJE DEL MATIZ. CÓMO NEGARSE A VER EL MUNDO EN BLANCO Y NEGRO. - Brahm, Sofía (Humanitas (07172168))
The essay "The Courage of Nuance: How to Refuse to See the World in Black and White" celebrates freedom of thought and the exploration of diverse points of view. The author, Jean Birbaum, highlights the importance of nuance in a time of ideological narrow-mindedness and mentions intellectuals such as Albert Camus, Georges Bernanos, and Hannah Arendt, who defended free and frank thinking. The text invites us to reflect on the importance of moderation, sincerity, and the ability to doubt in the search for truth.